Effect of Different Gel Etchants and Two Etching Times on Shear Bond Strength to Bovine Dentin of an Etch and Rinse 2-Step Adhesive System/Jose Gabriel M. Cadiz, Katherine S. Ejipto and Madeleine M. Rayos. - Cadiz, Jose Gabriel M.; Ejipto, Katherine S.; Rayos, Madeleine M.; Atienza, Angelina A. (2024)
INTRODUCTION: The COVID-19 pandemic has impacted the lives of individuals, changing
their daily routine due to implemented measures to prevent spread of the virus. These
measures have led to various challenges including limited access to dental care, thus
emphasizing the need for at-home preventive measures. This study aimed to compare the
oral hygiene practices (OHP) and oral health seeking behavior (OHSB) of students (A.Y
2022-2023) of University of the Philippines Manila (UPM) pre pandemic and during the
COVID-19 pandemic.
METHODS: A cross-sectional descriptive study on students of the UPM was conducted in
2022 using an online survey with a 3-part self-administered questionnaire. The online survey
was conducted in October to November of 2022.
RESULTS: The survey was completed by 51 UPM students from different colleges.
Participants showed ‘good’ to ‘very good’ OHP before and during the pandemic except on
flossing which showed ‘poor’ practice. They showed ‘positive’ to ‘very positive’ behavior
before and during the pandemic except the ‘neutral’ during the pandemic with regards to
visiting the dentist at least twice a year and for routine check up.
CONCLUSION: Results show that there is no significant difference with every oral hygiene
practice before and during the pandemic. In terms of the oral health seeking behavior, there
is a significant decrease in the number of respondents visiting the dentist at least twice
during the pandemic compared to before.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Shear bond strength